Comparative study of combined vitrectomy with phacoemulsification versus vitrectomy alone for primary full-thickness macular hole repair - Christophe Valmaggia; Filip Kostadinov; Corina Lang; Josef Guber (BMC Ophthalmology, 2021)
Abstract Background To assess the effectiveness and safety of 23-gauge pars plana vitrectomy combined with phacoemulsification versus vitrectomy alone in patients over 50 years with primary full-thickness macular holes (FTMH). Methods We retrospectively reviewed the medical records related to 406 consecutive vitrectomies performed for primary FTMH. Phacovitrectomy was performed in 294 phakic eyes whereas vitrectomy alone in 112 pseudophakic eyes. The cases were divided into three groups according to the stage of the FTMH: stage 2 (n = 93), stage 3 (n = 270), or stage 4 (n = 43). The primary outcome measure was the closure of the FTMH. The secondary outcome measures were the evolution of visual acuity as well as intraoperative and postoperative complications. Results Neither the primary nor the secondary outcomes differed between phacovitrectomy and vitrectomy alone for all three stages. The FTMH were closed in 375 eyes (92.4 %) after a first operation. The closure rate was higher for stage 2 (96.8 %) than for stages 3 (91.1 %) or 4 (90.75 %), but not significantly (P = 0.189). The mean visual acuity increased significantly from preoperatively LogMAR 0.68 (± SD 0.2) to LogMAR 0.43 (± SD 0.24) at the end of the follow-up (p < 0.001). Conclusions Combined 23-gauge pars plana vitrectomy with phacoemulsification for primary FTMH repair in patients over 50 years is as efficient and safe when compared with vitrectomy only. Trial registration The study was approved on 30th April 2020 by the local ethics committee (Ethikkommission Ostschweiz, EKOS 20/074; BASEC Nr. 2020-01033 ).